2021
DOI: 10.1155/2021/9987860
|View full text |Cite
|
Sign up to set email alerts
|

UV-Mediated Photofunctionalization of Indirect Restorative Materials Enhances Bonding to a Resin-Based Luting Agent

Abstract: Purpose. The potential of UV-mediated photofunctionalization to enhance the resin-based luting agent bonding performance to aged materials was investigated. Methods. Sixty samples of each material were prepared. Yttria-stabilized zirconia (YZr) and Pd-Au alloy (Pd-Au) plates were fabricated and sandblasted. Lithium disilicate glass-ceramic (LDS) was CAD-CAM prepared and ground with #800 SiC paper. Half of the specimens were immersed in machine oil for 24 h to simulate the carbon adsorption. Then, all of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…On another note, the UV light emitted by sunlight is not only valuable for general health, by stimulating the production of vitamin D in the skin, but it is particularly useful in the dental field, whether for the polymerization of biomaterials or for improving bonding in restorative dentistry [ 2 ] or osseointegration in implantology [ 3 ]. Given their virucidal, bactericidal, and fungicidal properties, UV was even recommended as a disinfection protocol during the COVID-19 pandemic for dental practices [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…On another note, the UV light emitted by sunlight is not only valuable for general health, by stimulating the production of vitamin D in the skin, but it is particularly useful in the dental field, whether for the polymerization of biomaterials or for improving bonding in restorative dentistry [ 2 ] or osseointegration in implantology [ 3 ]. Given their virucidal, bactericidal, and fungicidal properties, UV was even recommended as a disinfection protocol during the COVID-19 pandemic for dental practices [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of the bioactivity of CCM alloys by UV treatment has also been reported 13) , and surface modifications by UV irradiation have been used to improve the bonding ability of different dental materials. UV irradiation can decrease the contact angle of the Pd-Au surfaces and enhance the bond strengths of a resinbased luting cement 16) . Other studies also demonstrated that UV processing efficiently improves the bond strength between porcelain and titanium 17) , or composite resin and stainless steel crowns 18,19) .…”
Section: Introductionmentioning
confidence: 99%